2019
DOI: 10.1016/j.surg.2018.05.075
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with familial nonmedullary thyroid cancer present with more aggressive disease? Implications for initial surgical treatment

Abstract: Background: There are conflicting reports on whether familial nonmedullary thyroid cancer is more aggressive than sporadic nonmedullary thyroid cancer. Our aim was to determine if the clinical and pathologic characteristics of familial nonmedullary thyroid cancer are different than nonmedullary thyroid cancer. Methods: We compared patients with familial nonmedullary thyroid cancer to a cohort of 53,571 nonmedullary thyroid cancer patients from the Surveillance, Epidemiology, and End Results database. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
1
15
1
1
Order By: Relevance
“…From a histological viewpoint, there is no specific feature that distinguishes FNMTC from SNMTC [20], except in one report which showed that patients in the FNMTC group had more significantly classic variant PTC than those in the sporadic PTC group (84% vs. 63.3%; P < 0.001) [7]. We found that all the affected individuals in the reported family had classic variant PTC, except one who had a follicular variant PTC.…”
Section: Histopathological Featurescontrasting
confidence: 50%
See 1 more Smart Citation
“…From a histological viewpoint, there is no specific feature that distinguishes FNMTC from SNMTC [20], except in one report which showed that patients in the FNMTC group had more significantly classic variant PTC than those in the sporadic PTC group (84% vs. 63.3%; P < 0.001) [7]. We found that all the affected individuals in the reported family had classic variant PTC, except one who had a follicular variant PTC.…”
Section: Histopathological Featurescontrasting
confidence: 50%
“…Most PTC cases are sporadic; however, 5-10% are familial [2,3], and like the sporadic form, females are 2-3 times more affected than males [4][5][6]. Familial PTC (FPTC) is the most common type of familial nonmedullary thyroid cancer (FNMTC) [7], which is identified, in most studies, when two or more first-degree relatives are diagnosed with the condition in the absence of a history of familial syndromes or risk factors that are commonly associated with NMTC [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the rare syndromic forms of familial NMTC (FNMTC), including familial adenomatous polyposis, Gardner syndrome, Cowden syndrome, Carney complex type 1, Werner syndrome, and DICER1 syndrome, the genetic basis of FNMTC is largely unknown [2,3]. FNMTC has been associated with an earlier age of onset, a higher incidence of multifocality, and more aggressive disease compared to its sporadic counterpart [4,5]. Thus, it is important to identify genetic factors behind the familial disease to facilitate genetic counseling and clinical management of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Further, based on their results, these authors suggest that surgical treatment should be more aggressive for patients with FNMTC [7]; however, a retrospective study by Pitoia et al (2011) did not detect statistically significant differences in age at diagnosis, sex, tumor size, tumor stage or distant metastasis between patients with familial and sporadic NMTC. The only differences in the baseline characteristics observed between the two groups were in bilateral malignancy (38% vs. 24%, respectively; p = 0.03), lymph node metastasis (56.2% vs. 39%, respectively; p = 0.01), and multicentricity (43% vs. 28%, respectively; p = 0.03) [6]; however, Moses et al (2011) suggest that patients with FNMTC present at a significantly younger age (an average of 5 years younger) than those with sporadic thyroid cancer, although no other statistically significant differences are detected.…”
Section: Introductionmentioning
confidence: 99%